Winnowing fan blade head injury: a farm mishap (Journal of Society of Surgeons of Nepal, 2017)
In an agriculture based economy like Nepal farm related accidents are not uncommon. Indigenous farm machinery like winnowing fan is common in our villages. Five cases of fan related head injuries presenting to the Department of Surgery, Tribhuvan University Teaching Hospital in a single month of winnowing season are discussed.JSSN 2015; 18 (1), Page: 29-31